PSYCHOLOGICAL IMPACTS OF FETAL MALFORMATION ON THE SUPPORT NETWORK: THE PERSPECTIVE OF THE PREGNANT WOMAN - Kiriki, Raíssa Cinti; Rodrigues, Débora Grigolette; Pinto, Maria Jaqueline Coelho; Menezes, Lucas Teixeira; Zanin, Carla Rodrigues; Lucânia-Dionísio, Eliane Regina (Seven Editora, 2025)
Introduction: Fetal malformation consists of a functional, organic, or genetic alteration in the fetus and can be identified before birth, allowing for early care. Its occurrence causes distress in the pregnant woman or couple and requires family preparation for the arrival of a baby who will need specialized care, often intensive, surgical, and, in some cases, palliative. Objective: To analyze, from the perspective of the pregnant woman, the psychological effects that fetal malformation has on her support network. Methodology: This is a cross-sectional, descriptive, qualitative study conducted in a high-risk pregnancy clinic and in the ultrasound examination department of a maternal and child teaching hospital in a city in the interior of the state of São Paulo. The study was conducted with 11 pregnant women being monitored by a fetal medicine team due to a diagnosis of fetal malformation. The instruments used were: a sociodemographic, obstetric, and family questionnaire and a structured open interview, analyzed by Content Analysis. Results: The results showed the sociodemographic, obstetric, and family profile of the participants, as well as five thematic categories developed from the analysis of the reports. It was concluded that, in most cases, the support network was able to strengthen the pregnant woman, but in others, fragility was identified. Difficulties in adapting the support network in the face of external/visible malformations and genetic syndromes were identified. The reports showed shared coping strategies such as religiosity, doctor-patient relationship, and quality health care. In addition, most participants reported playing a key role in reducing distressing fantasies related to fetal malformation, favoring the integration between the idealized baby and the real baby in the family group. Finally, the study highlights the importance of the presence of the support network in prenatal consultations and exams, as well as the use of light technologies in maternal and child health care. DOI: https://doi.org/10.56238/sevened2025.021-029